Meningkatkan Hasil Belajar IPA Tema Bunyi dan Sumber Bunyi Dengan Model Snoball Throwing Pada Siswa Kelas IV SD Negeri 14 Kota Ternate - Apridayani Marasabessy (Peneliti.net, 2023)
The problem in this research is how to improve the science learning outcomes with the theme of Sound and Sound Sources with the snoball throwing model for fourth grade students at SD Negeri 14 Kota Ternate. The purpose of this study was to determine the increase in learning outcomes in science with the theme of Sound and Sound Sources with the snoball throwing model for fourth grade students at SD Negeri 14 Kota Ternate. This type of research is Classroom Action Research which consists of 4 stages, namely, planning, implementing action, observing and reflecting. This research was conducted in 2 cycles. The subjects in this study were class IV with a total of 29 students, consisting of 15 girls and 14 boys. Data collection was carried out using observation sheets in the learning process, namely to find out the increase in the student learning process using test sheets to find out the increase in student learning outcomes and documentation. Based on the description of the research results and discussion in chapter IV which describes that research using the snowball throwing learning model on the theme of sound and sound sources can improve science learning outcomes in fourth grade students of SD Negeri 14 Ternate City. Student learning outcomes in cycle I with an average value of 75-85 or with a complete learning outcome of 78.27%. Student learning outcomes in cycle I have met the indicators because with enthusiasm and enthusiasm students follow the learning well. however, it does not meet the KKM standards set by the researcher. Therefore, the next learning improvement action is carried out, namely cycle II. The achievement of learning outcomes in cycle II increased with an average score of 85 – 95 or with learning completeness of 87.75%, with a total increase of 9.48%. This success can be seen from the comparison in each cycle I and cycle II with very good qualifications.